Use of Aqueous Extract of Wrightia tinctoria Leaves and Coconut Oil in Camel Mange - Pandya, N. R.; Mandali, G. C.; Dave, K. M.; Raval, S. K. (International Journal of Bio-resource and Stress Management, 2021)
The present study was carried out during August 2019 to March 2020 for the diagnosis and therapeutic management of mange in camel. A total of fourteen positive cases of mange infestation were selected for the therapeutic trial. The therapeutic trial was carried out with the use of two different treatment viz., aqueous extract of Wrightia tinctoria (20%) and coconut oil in mangy camels. The mite count was performed on weekly interval up to five weeks. The camels had more than twenty Sarcoptic mites on day 0 (pre-treatment). The mite count was gradually decreased on fifth week and the mite reduction was 96.50% and 96.77% in group A & B, respectively. The haematology shows the significantly (p<0.05) increase in Hb, TEC, PCV, Neutrophils and Monocytes whereas, significantly (p<0.05) decreased in TLC, and Lymphocyte. The serological and mineral estimation shows the significant (p<0.05) increase in values of total protein, ALT and Zinc; whereas creatinine, AST and copper were decreased significantly (p<0.05). After treatment of mange infected camels with two different treatments the values of all these hemato-biochemical and micromineral constituents returned nearer to normal values of camels. Thus, aqueous extract of Wrightia tinctoria (20%) and coconut oil gave positive effect on mange infested camels.